The causes of gender diversity in Malaysian large firms - Abdullah, Shamsul Nahar (Springer, 2014)
The issue of women’s representation at the decision-making level in Malaysia has received special attention from the Government since 2004, the year in which it adopted a policy requiring that 30 per cent of the posts at the decision-making level in the public sector be filled by women. In 2011, the policy was extended to the private sector where 30 per cent of listed firms’ board seats are to be allocated to women with 2016 being the deadline for compliance. To this end, this paper aims at examining the factors that determine the appointment of women to the boards of Malaysian large firms. Large firms were chosen in this study because they have the resources and the capacity to adopt the policy more readily than smaller firms. The results reveal that gender diversity is positively associated with board size and the presence of family on the board. That is, the larger the board, the more likely it is that women sit on it. The fact that the presence of women on the board is associated with the presence of one or more family members on the board means that the appointment of women to the board is very much influenced by family ties rather than commercial reasons. The results also reveal a positive association between board independence and the proportion of women directors. Further, it is found that board independence is associated positively with the presence of independent women directors. Finally, the results show that firm performance is negatively associated with gender diversity. That is, firms with low financial performance are more likely to have women on their boards. Hence, taken altogether, the evidence suggests that the appointment of women to the board is very much driven by tokenism and family connection rather than by the business case.